Optical properties of colloidal crystals with structural colors on paper substrates using a rapid coating technology. Issue 4 (21st April 2021) - Pan, Jie; Huang, Min; Xi, Yonghui; Li, Xiu
Abstract: Structural colors generated by colloidal crystals offer a promising method to create large-scale nanostructures due to their stability in comparison with dyes and pigments. However, the low durability and the low efficiency of colloidal crystals limit their practical applications. In this work, a rapid coating technology was applied in fabricating colloidal crystals on paper substrates with silicon dioxide microspheres in order to develop a fast and efficient method to produce structural colors. It was confirmed that the silicon dioxide colloidal microspheres could form a uniform photonic crystal film on papers in the end of the assembly process, and the formation mechanism of photonic crystal on papers were proposed. The optical properties of structural colors on papers were investigated and the position of photonic band gap was characterized. The results showed that the varied structural colors across the visible region confirmed by reflectance spectra could be adjusted by controlling the sizes of the microspheres and viewing angles, and this was consistent with the law of the Bragg diffraction. The CIE1976L*a*b* values of the structural colors were in agreement with their reflectance spectra. The rapid coating technology producing colloidal crystals is efficient with low cost and high adhesion, which can be used in the design and application of green printing and packaging industries.